Pengaruh Jejaring Usaha Dan Teknologi Informasi Terhadap Kinerja Umkm Sapu Lidi Dan Sapu Ijuk Di Desa Medan Sinembah Kecamatan Tanjung Morawa - Ilmiati, Ilmiati; Nasution, Lukman; Habra, Dani; Hsb, Melisa (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This research aims to determine the influence of business networks and information technology on the performance of Sapu Lidi and Sapu Ijuk MSMEs in Medan Sinembah Village, Tanjung Morawa District. The sample for this research was 30 Broom Stick and Broom Fiber MSMEs in Medan Sinembah Village, Tanjung Morawa District. The analysis techniques used are Multiple Regression, T Test, F Test and Coefficient of Determination. The analysis results were obtained using the multiple linear regression equation, namely Y = 16.064 + 0.290X1 + 0.101X2. The t value of the Business Network variable (X1) is 4.654 when compared to the t table value of 1.703. So the calculated t obtained is greater than the t table value or 4.654 > 1.703. Then it can also be seen that the sig value is smaller than the value 0.00 < 0.05, so Ho is rejected and Ha is accepted so that the variable 1,703. So the calculated t obtained is greater than the t table value or 2.025 > 1.703. Then it can also be seen that the sig value is smaller than the probability value of 0.00 < 0.05, so Ho is rejected and Ha is accepted so that the variable 00>0.05 and Fcount value 96.467>Ftable 2.96. R square (R2) or R square shows the coefficient of determination is 0.877, meaning that the percentage of Business Networks (X1) and Information Technology (X2) on increasing MSME performance is 87.7% while the remaining 12.3% is influenced by other variables not examined by the this research.